Community health worker roles in intervention delivery: a scoping review of heart disease and stroke prevention trials in the United States - Naqvi, Imama A.; Bassile, Clare C.; Ebadi, S. Reza; Hoyte, Dakembay E.; Paguirigan, Lauren N.; Meyreles, Juan; McMillan, Glenn; Kronish, Ian M.; Williams, Olajide A. (Frontiers in Stroke, 2025)
Heart disease (HD) and stroke risk can be reduced with adequate cardiovascular disease (CVD) disease prevention as outlined in the American Heart Association's Life's Essential 8 guidelines for modifiable health behaviors. This scoping review examines the roles of community health workers (CHWs) in CVD prevention trials across the United States. In the 24 clinical trials identified, our review emphasizes the effectiveness of CHWs in improving health behaviors and outcomes, particularly for underserved populations with limited access to health care. CHWs were actively engaged in implementing interventions, providing culturally sensitive education, offering health coaching, and supporting lifestyle modifications, such as increased physical activity and medication compliance. Notably, while most studies focused on HD, only three specifically targeted secondary stroke prevention. Beyond their role of delivering behavioral interventions, CHWs supported research efforts by collecting data and maintaining participant involvement. However, their integration into academic teams was inconsistent in terms of scope of practice and level of interprofessional engagement. Furthermore, CHW research contributions were rarely recognized, with a handful acknowledged in publications. Training for CHWs generally included disease-specific knowledge and communication skills. CHW training programs varied considerably in their scope and standards, with unclear role definitions and insufficient collaboration with academic institutions. To enhance CHW-led preventive health care, developing standardized training frameworks, defining CHW responsibilities in clinical and research collaborations and building sustainable community–academic partnerships are suggested. These actions could significantly increase CHWs' role in reducing CVD disparities, thereby promoting more equitable health care across the United States.